The peptide antibiotic LL-37/hCAP-18 is expressed in epithelia of the human lung where it has broad antimicrobial activity at the airway surface - Bals, Robert (The National Academy of Sciences, 1998)
The airway surface is an important host defense against pulmonary infection. Secretion of proteins with antimicrobial activity from epithelial cells onto the airway surface represents an important component of this innate immune system. Defensins are the best characterized epithelial-derived peptide antibiotics. A member of another family of peptide antibiotics called cathelicidins recently was identified from human bone marrow. We show in this paper that this human peptide named LL-37/hCAP-18 also may play a role in innate immunity of the human lung. In situ hybridization localized high levels of LL-37/hCAP-18 RNA to surface epithelial cells of the conducting airway as well as serous and mucous cells of the submucosal glands. LL-37/hCAP-18 peptide with antimicrobial activity was partially purified from airway surface fluid from human lung and a human bronchial xenograft model. The synthetic peptide LL-37 demonstrated antibiotic activity against a number of Gram-negative and Gram-positive organisms including Pseudomonas aeruginosa; bacterial killing of LL-37 was sensitive to NaCl and was synergistic with lactoferrin and lysozyme. In summary, we show that LL-37/hCAP-18 is a peptide with broad antimicrobial activity that is secreted onto the airway surface from epithelial cells of the human lung.